A positive electrode current collector and a method for preparing the same
By alternately setting the porous metal aluminum layer and alumina layer in the positive electrode current collector of the lithium-ion battery, the problem of local short circuit and thermal runaway in the nail-piercing experiment of lithium-ion batteries is solved, and a higher nail-piercing pass rate and lower resistivity are achieved, improving the safety performance of the battery.
Patent Information
- Application Number
- CN202110181978.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-07
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-02-07
AI Technical Summary
Lithium-ion batteries are prone to local short circuits and thermal runaway in nail-through experiments, the resistivity of existing porous metal foil current collector increases, and the metal foil is poor in density and is prone to fall off.
Using a positive electrode current collector including a base film, a multi-layer metal aluminum layer and a multi-layer aluminum oxide layer, the porous metal aluminum layer and an alumina layer are alternately arranged to ensure that the pores of the thorn oxide layer are conducted, the formation of metal burrs is reduced, and the bonding fastness between the metal aluminum layer and the base film is improved.
The pass rate of the nail penetration experiment is improved, the resistivity of the positive electrode current collector is reduced, the bonding force between the metal aluminum layer and the base film is enhanced, and the safety performance of the battery is improved.
Smart Images

Figure CN112751036B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of current collectors for lithium-ion batteries, and in particular to a positive electrode current collector and a preparation method thereof. Background Art
[0002] With the widespread application of lithium batteries in new energy vehicles and other fields, their safety issues are becoming more and more concerned. Internal short circuit of the battery is a very dangerous situation, and nail penetration test is usually used to simulate internal short circuit. For lithium-ion battery safety testing, nail penetration test is more troublesome. The energy of the entire battery will be released through this short circuit point in a short time (up to 70% of the energy will be released within 60s), which will cause the temperature of the short circuit point to rise sharply in a short time, and then trigger a chain reaction, leading to thermal runaway. The nail penetration test is to use a nail to penetrate the center of the battery after the battery is fully charged. When the nail penetrates the current collector, it will pierce the metal layer of the current collector, thereby forming burrs on the metal layer, resulting in local short circuit, rapid temperature rise, and battery combustion or even explosion.
[0003] Patent document with application number 201720508539.7 provides a current collector, which improves the nail penetration rate of the electrochemical energy storage device by setting a porous metal foil to increase the safety performance of the electrochemical energy storage device. Summary of the invention
[0004] The inventors have found that since the metal foil has a porous structure, the resistivity of the current collector will increase, reducing the current conduction effect; and the metal foil has poor density and is easy to fall off the base film.
[0005] The purpose of the present application is to provide a positive electrode current collector and a preparation method thereof, which can increase the pass rate of the nail penetration test and improve the bonding strength between the metal aluminum layer and the base film, and the resistivity is relatively low.
[0006] In a first aspect, the present application provides a positive electrode current collector, comprising a base film, a multi-layer metal aluminum layer and a multi-layer aluminum oxide layer. Aluminum oxide layers and metal aluminum layers are alternately overlapped on at least one surface of the base film, the metal aluminum layer is a porous structure, and the two metal aluminum layers on the two surfaces of the aluminum oxide layer are connected through the holes on the aluminum oxide layer.
[0007] The layer in contact with the base film is an aluminum oxide layer, which can improve the bonding strength between other layer structures (layer structures other than the base film) and the base film. The porous metal aluminum layer and the aluminum oxide layer are arranged alternately. During the nail penetration test, the iron nail can pass through the positive electrode current collector along the pore structure of the metal aluminum layer and the interface of the aluminum oxide layer, avoiding the formation of metal burrs, reducing the occurrence of local short circuits, and improving the nail penetration rate. And this staggered overlapping arrangement can also reduce the resistivity of the positive electrode current collector.
[0008] In a possible implementation, the total thickness of the aluminum oxide layer is 1%-20% of the total thickness of the metal aluminum layer. The thickness of the metal aluminum layer is thicker and the thickness of the aluminum oxide layer is thinner, which can ensure the conductivity of the positive electrode current collector.
[0009] In a possible implementation manner, the total thickness of the metal aluminum layer and the aluminum oxide layer is 600-2400 nm, the number of the metal aluminum layer is 10-30 layers, and the number of the aluminum oxide layer is 10-30 layers.
[0010] The nail penetration rate can be higher and the resistivity of the positive electrode collector can be smaller.
[0011] In a possible implementation, the thickness of the base film is 2.6-12 μm, so as to form a multi-layer structure on the base film.
[0012] In one possible embodiment, the base film is selected from one of OPP film, PET film, PI film, PS film, PPS film, CPP film, PEN film, PVC film, PP film, PE film and non-woven fabric film.
[0013] In a possible implementation, aluminum oxide layers and metal aluminum layers are alternately overlapped and arranged on both surfaces of the base film. Both surfaces can conduct current to increase the energy density of the battery.
[0014] In one possible embodiment, the resistivity of the positive electrode current collector is (5.0-15.0)×10 -8 Ω.m. The resistivity of the positive electrode current collector is low and the nail penetration rate is high.
[0015] In a second aspect, the present application provides a method for preparing a positive electrode current collector, comprising: forming an aluminum oxide layer and a metal aluminum layer having a porous structure by alternating overlapping in sequence on at least one surface of a base film, and the two metal aluminum layers on the two surfaces of the formed aluminum oxide layer are connected through the holes on the aluminum oxide layer.
[0016] It can increase the passing rate of the nail penetration test, improve the bonding strength between the metal aluminum layer and the base film, and the resistivity is relatively low.
[0017] In a possible implementation, the method for forming a metal aluminum layer having a porous structure comprises: the vacuum degree of the coating environment is (1.0-9.0)×10 -1 Pa.
[0018] By controlling the vacuum degree within the above range, a porous structure can be formed on the metal aluminum layer, and the compactness and conductivity of the positive electrode current collector are both met.
[0019] In a possible implementation, the method for forming an aluminum oxide layer includes: firstly adsorbing oxygen on the surface of a vapor-deposited film, and then reacting the vapor-deposited aluminum atoms with the oxygen to form an aluminum oxide layer on the surface of the vapor-deposited film.
[0020] Oxygen is first adsorbed on the surface of the evaporated film, and then aluminum atoms react with oxygen through evaporation to form an aluminum oxide layer structure, so that a thinner aluminum oxide layer can be obtained and the aluminum oxide layer can be made more uniform.
[0021] In a possible implementation manner, when the aluminum oxide layer in contact with the surface of the base film is formed, the vacuum degree of the coating environment is (1.0-9.0)×10 -2 Pa; when the aluminum oxide layer that does not contact the surface of the base film is formed, the vacuum degree of the coating environment is (1.0-9.0)×10 -1 Pa.
[0022] The aluminum oxide layer close to the base film can be made denser to increase the bonding strength between the layer structure and the base film. In addition, other aluminum oxide layers can have certain holes, so that the two metal aluminum layers on the two surfaces of the aluminum oxide layer are conductive to meet the flow conduction effect of the positive electrode collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, without paying any creative work, other related drawings can be obtained based on these drawings and they also belong to the protection scope of the present application.
[0024] Figure 1 A schematic diagram of the layer structure of the positive electrode current collector provided in this application;
[0025] Figure 2 This is a schematic diagram of the structure of the coating component in the evaporation coating equipment provided in this application.
[0026] Icons: 110-base film; 120-metal aluminum layer; 130-aluminum oxide layer; 111-first surface; 112-second surface; 210-unwinding roller; 221-first passing roller; 222-second passing roller; 223-third passing roller; 224-fourth passing roller; 230-arc roller; 240-main cold roller; 251-fifth passing roller; 252-sixth passing roller; 253-seventh passing roller; 254-eighth passing roller; 260-winding roller; 270-evaporation source; 280-ventilation device. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0028] Figure 1This is a schematic diagram of the layer structure of the positive electrode current collector provided in this application. Figure 1 In the present application, the positive electrode current collector includes a base film 110 , a metal aluminum layer 120 and an aluminum oxide layer 130 .
[0029] Optionally, the thickness of the base film 110 is 2.6-12 μm. Further, the thickness of the base film 110 is 2.6-5 μm, 5-8 μm or 8-12 μm. Exemplarily, the thickness of the base film 110 is 2.6 μm, 3 μm, 5 μm, 6.5 μm, 8 μm, 10 μm or 12 μm.
[0030] The base film 110 is selected from one of OPP (o-phenylphenol) film, PET (polyethylene terephthalate) film, PI (polyimide) film, PS (polystyrene) film, PPS (polyphenylene sulfide) film, CPP (cast polypropylene) film, PEN (polyethylene naphthalate diformicacid glycol ester) film, PVC (polyvinyl chloride) film, BOPP (biaxially oriented polypropylene) film, PE (polyethylene) film and non-woven film.
[0031] In the present application, the base film 110 has a first surface 111 and a second surface 112 along the thickness direction of the base film 110. Aluminum oxide layers 130 and metal aluminum layers 120 may be alternately overlapped on the first surface 111 of the base film 110; that is, aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, and metal aluminum layers 120 may be overlapped on the first surface 111 of the base film 110. The aluminum oxide layers 130 may have multiple layers, and the metal aluminum layers 120 may also have multiple layers.
[0032] Aluminum oxide layers 130 and metal aluminum layers 120 may also be alternately overlapped on the second surface 112 of the base film 110; that is, aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, and metal aluminum layers 120 may be alternately overlapped on the second surface 112 of the base film 110. The aluminum oxide layers 130 may have multiple layers, and the metal aluminum layers 120 may also have multiple layers.
[0033] Aluminum oxide layers 130 and metal aluminum layers 120 may also be alternately overlapped on the first surface 111 and the second surface 112 of the base film 110; that is, aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, and metal aluminum layers 120 may be overlapped on the first surface 111 of the base film 110, and aluminum oxide layers 130, metal aluminum layers 120, aluminum oxide layers 130, and metal aluminum layers 120 may be overlapped on the second titanium oxide surface of the base film 110. On either side of the base film 110, the aluminum oxide layer 130 may have multiple layers, and the metal aluminum layer 120 may have multiple layers ( Figure 1 The two surfaces of the base film 110 of the positive electrode collector shown in the figure are respectively provided with two aluminum oxide layers 130 and two metal aluminum layers 120, but this is only an example and does not limit the number of aluminum oxide layers 130 and the number of metal aluminum layers 120).
[0034] The layer structures on the surface of the base film 110 are all aluminum oxide layers 130 (the layer in contact with the base film 110 is all aluminum oxide layers 130 ), which can improve the bonding strength between other layer structures (layer structures other than the base film 110 ) and the base film 110 .
[0035] In the present application, the metal aluminum layer 120 is a porous structure, and the two metal aluminum layers 120 on the two surfaces of the aluminum oxide layer 130 are connected through the holes on the aluminum oxide layer 130. The porous metal aluminum layer 120 and the aluminum oxide layer 130 are arranged alternately. During the nail penetration experiment, the iron nail can pass through the positive electrode current collector along the pore structure of the metal aluminum layer 120 and the interface of the aluminum oxide layer 130, avoiding the formation of metal burrs, reducing the occurrence of local short circuits, and improving the nail penetration rate. And this staggered overlapping arrangement can also reduce the resistivity of the positive electrode current collector.
[0036] Optionally, the aluminum oxide layer 130 contacting the first surface 111 and the second surface 112 of the base film 110 is a dense structure, which is substantially free of holes, and can improve the bonding strength between the aluminum oxide layer 130 and the base film 110. In other embodiments, the aluminum oxide layer 130 contacting the first surface 111 and the second surface 112 of the base film 110 can also be a structure with holes, which is not limited in the present application.
[0037] The aluminum oxide layer 130 that is not in contact with the first surface 111 and the second surface 112 of the base film 110 has a porous structure, which can make the two adjacent metal aluminum layers 120 of the aluminum oxide layer 130 conductive. It should be noted that it is not necessary for all metal aluminum layers 120 to be conductive, and only some of the multiple metal aluminum layers 120 can be conductive.
[0038] Optionally, the total thickness of the aluminum oxide layer 130 is 1%-20% of the total thickness of the metal aluminum layer 120. Further, the total thickness of the aluminum oxide layer 130 is 1%-5%, 5%-10%, 10%-15% or 15%-20% of the total thickness of the metal aluminum layer 120. Exemplarily, the total thickness of the aluminum oxide layer 130 is 1%, 3%, 5%, 7%, 10%, 13%, 15%, 18% or 20% of the total thickness of the metal aluminum layer 120.
[0039] In the present application, the total thickness of the metal aluminum layer 120 and the aluminum oxide layer 130 is 600-2400 nm, the number of layers of the metal aluminum layer 120 is 10-30 layers, and the number of layers of the aluminum oxide layer 130 is 10-30 layers.
[0040] Optionally, the total thickness of the metal aluminum layer 120 and the aluminum oxide layer 130 on the first surface 111 of the base film 110 is 600-1200 nm; the total thickness of the metal aluminum layer 120 and the aluminum oxide layer 130 on the second surface 112 of the base film 110 is also 600-1200 nm.
[0041] By limiting the number of layers and the total thickness, the resistivity of the positive electrode current collector can be (5.0-15.0)×10 -8 Ω.m, and the nail penetration rate of the battery cell is high.
[0042] The method for preparing the positive electrode current collector includes alternately forming an aluminum oxide layer 130 and a metal aluminum layer 120 with a porous structure on at least one surface of a base film 110, and the two metal aluminum layers 120 on both surfaces of the formed aluminum oxide layer 130 are conductive.
[0043] In order to prepare the above-mentioned positive electrode current collector, the inventors improved the evaporation coating equipment for preparing the positive electrode current collector as follows:
[0044] Figure 2 This is a schematic diagram of the structure of the coating component in the evaporation coating equipment provided in this application. Figure 2 The evaporation coating device includes a chamber and a coating assembly arranged in the chamber. Before coating, the base film 110 is first arranged on the coating assembly along the conveying path (when the base film 110 is fixed on the coating assembly, the first surface 111 and the coating assembly roller can be attached or the second surface 112 and the coating assembly roller can be attached), and then the air in the chamber is extracted using a vacuum pump to make the chamber in a vacuum state, providing a vacuum environment for the coating assembly, so as to evaporate the base film 110. The vacuum degree in the chamber can be controlled by the amount of air extracted by the vacuum pump, and can be adjusted according to demand.
[0045] The coating assembly includes a unwinding roller 210 arranged in sequence along the conveying path of the base film 110, multiple rollers (the first roller 221, the second roller 222, the third roller 223 and the fourth roller 224 along the conveying path, the number of rollers is not limited and can be modified according to actual needs, and the four rollers here are just an example), an arc roller 230, a main cold roller 240, multiple rollers (the fifth roller 251, the sixth roller 252, the seventh roller 253 and the eighth roller 254 along the conveying path, the number of rollers is not limited and can be modified according to actual needs, and the four rollers here are just an example) and a winding roller 260.
[0046] The base film 110 is set up, and the base film 110 set between the arc roller 230 and the roller (the fourth roller 224) at the front end of the arc roller 230 is in a basically horizontal state. An evaporation source 270 is set under the base film 110 to uniformly metal-plate the base film 110.
[0047] Optionally, the evaporation source 270 here is an aluminum evaporation source, which can be an aluminum wire or an aluminum metal block, which is not limited in this application. If it is an aluminum wire, a wire feeding mechanism ( Figure 2 (not shown) continuously feeds the aluminum wire.
[0048] In the present application, a ventilator 280 is provided at the front end of the evaporation source 270, and the ventilator 280 is located below the base film 110. Optionally, the base film 110 above the ventilator 280 is also substantially in a horizontal state, and the ventilator 280 is mainly used to introduce oxygen so that oxygen is adsorbed on the surface of the base film 110.
[0049] Optionally, the air outlet pipe of the ventilation device 280 is a horizontal pipe, the axial direction of the horizontal pipe is consistent with the width direction of the base membrane 110, and multiple air outlets are arranged on the side of the horizontal pipe close to the base membrane 110. The distances between the multiple air outlets and the horizontally running base membrane 110 are basically consistent. Oxygen is evenly discharged through the multiple air outlets so that oxygen is more evenly adsorbed on the surface of the base membrane 110.
[0050] Optionally, if the width of the base film 110 is 1.2-1.65 m, the air flow of the ventilation device 280 is 100-1500 sccm, so that the surface of the base film 110 can be substantially uniformly attached with oxygen.
[0051] The specific method for preparing the above-mentioned positive electrode current collector using the above-mentioned equipment is as follows:
[0052] S10, adjust the vacuum degree in the chamber to (1.0-9.0)×10 -2Pa (large vacuum degree) causes the first surface 111 of the base film 110 to move to above the ventilation device 280, and oxygen is introduced through the ventilation device 280 to be adsorbed on the first surface 111 of the base film 110. Then, the base film 110 continues to move to above the evaporation source 270, and the evaporation source 270 evaporates the aluminum wire. The aluminum atoms move upward onto the base film 110, and react with the oxygen adsorbed on the first surface 111 of the base film 110 to form an aluminum oxide layer 130, which is then cooled by the main cold roller 240 and then rolled up after passing through the roller.
[0053] The generated aluminum oxide layer 130 is obtained by reacting uniformly adsorbed oxygen with aluminum atoms, which can make the thickness of the aluminum oxide layer 130 thinner and more uniform. At the same time, controlling the vacuum degree within the above range can make the obtained aluminum oxide layer 130 more compact, so as to make the base film 110 more bonded to other layer structures.
[0054] S20, adjust the vacuum degree in the chamber to (1.0-9.0)×10 -1 Pa (the vacuum degree is relatively small), so that the first surface 111 of the evaporated film (wherein the evaporated film is the base film 110 and the aluminum oxide layer 130 contacting the base film 110, and the first surface of the evaporated film refers to the surface of the aforementioned aluminum oxide layer 130 away from the base film 110) runs to the top of the evaporation source 270 (at this time, the ventilation device 280 is closed), so that the evaporation source 270 evaporates the aluminum wire, and the aluminum atoms move upward to the evaporated film, forming a metal aluminum layer 120 on the first surface of the evaporated film, which is then cooled by the main cold roller 240 and then rolled up after passing through the roller.
[0055] Since the vacuum degree when the metal aluminum layer 120 is formed is relatively small, the formed metal aluminum layer 120 can have a porous structure, which is beneficial to increase the nail penetration rate.
[0056] S30, continue to maintain the vacuum degree at (1.0-9.0)×10 -1 Pa, the first surface of the evaporated film (wherein the evaporated film is the base film 110 and the aluminum oxide layer 130 contacting the base film 110 and the metal aluminum layer 120 contacting the aluminum oxide layer 130, and the first surface of the evaporated film refers to the surface of the metal aluminum layer 120 away from the base film 110) is run to the top of the ventilation device 280, and oxygen is introduced through the ventilation device 280 to adsorb the oxygen on the first surface of the evaporated film, and then the evaporated film continues to run to the top of the evaporation source 270, so that the evaporation source 270 evaporates aluminum wire, and aluminum atoms move upward to the evaporated film, react with the oxygen adsorbed on the first surface 111 of the evaporated film to form the aluminum oxide layer 130, and then it is cooled by the main cold roller 240, and then rolled up after passing through the roller.
[0057] Since the vacuum degree is relatively low when the metal aluminum layer 120 is formed, the formed aluminum oxide layer 130 can have a porous structure, which is beneficial to increase the nail penetration rate and enable the two adjacent metal aluminum layers 120 of the aluminum oxide layer 130 to be conductive, so that the resistivity of the positive electrode current collector is relatively low. At the same time, the thickness of the generated aluminum oxide layer 130 is relatively thin and uniform.
[0058] S40, continue to sequentially form the metal aluminum layer 120 and the aluminum oxide layer 130, and perform coating for 10-30 times in total, so that the total thickness of the metal aluminum layer 120 and the aluminum oxide layer 130 on the first surface 111 of the base film 110 is 600-1200 nm.
[0059] S50, continue to perform coating on the second surface 112 of the base film 110 for 10-30 times by the above method, so that the total thickness of the metal aluminum layer 120 and the aluminum oxide layer 130 on the second draft surface of the base film 110 is 600-1200nm.
[0060] It should be noted that the above method is to first coat the first surface 111 of the base film 110, and then coat the second surface 112 of the base film 110. Alternatively, a layer of film is firstly coated on the first surface 111 of the base film 110, and then a layer of film is coated on the second surface 112 of the base film 110, and then films are sequentially coated on the first surface 111 and the second surface 112. The present application does not limit the order of coating on the first surface 111 and the second surface 112.
[0061] Example
[0062] The positive electrode current collector is prepared using the above-mentioned equipment, and the preparation method includes the following steps:
[0063] A PET film with a thickness of 8 μm and a width of 1.5 m is placed on the coating assembly, and the PET film passes through the unwinding roller, the first roller, the second roller, the third roller, the fourth roller, the arc roller, the main cold roller, the fifth roller, the sixth roller, the seventh roller, the eighth roller and the winding roller in sequence.
[0064] A ventilation device and an evaporation source are sequentially arranged below the horizontal PET film passing through the fourth roller and the arc roller. During the operation, the PET film first passes through the ventilation device and then passes through the evaporation source. The preparation conditions of the positive electrode current collector are shown in Table 1.
[0065] Table 1 Preparation conditions of positive electrode current collector
[0066]
[0067]
[0068] The properties of the positive electrode current collectors prepared in the above embodiments and comparative examples were tested to obtain Table 2. The bonding strength test method is as follows: (1) a fixed type of 3M tape is used, and a fixed pressure wheel is used to press the film surface firmly; (2) on a tensile machine, the film is pulled at an angle of 180° in the opposite direction. In the bonding strength data, different pulling speeds are tested. On the premise that the surface layer is not peeled off, the higher the speed, the better the bonding strength; × represents that the bonding strength is very low and cannot be tested.
[0069] The resistivity of the current collector is tested by using a four-probe method to measure the square resistance of the current collector to obtain the square resistance Rs, in Ω. The thickness d of the current collector functional layer is the difference between the total thickness of the current collector and the thickness of the base film, and the resistivity ρ = Rs × d, in Ω.m.
[0070] The core roll was prepared using the positive electrode current collector, and the lithium-ion battery was prepared. The nail penetration rate of the lithium-ion battery was tested as shown in Table 2.
[0071] Wherein, the preparation of lithium ion battery is as follows:
[0072] Preparation of positive electrode sheets: The positive electrode slurry (a slurry consisting of lithium iron phosphate (LFP), acrylic resin (PAA), positive electrode binder polyvinylidene fluoride (PVDF), positive electrode conductive agent conductive carbon black (Super P), carbon nanotubes (CNT) and N-methylpyrrolidone (NMP) in a mass ratio of 75:5:5:5:5:5) is evenly coated on the above-mentioned positive electrode collector (example and comparative example), dried at room temperature, transferred to a 120°C oven for drying for 1 h, and then cold pressed and cut to obtain the positive electrode sheets.
[0073] Preparation of negative electrode sheets: The negative electrode slurry (a slurry composed of components with a mass ratio of 85:5:5:5 among graphite, negative electrode conductive agent conductive carbon black (Super P), thickener sodium carboxymethyl cellulose (CMC), and negative electrode binder styrene-butadiene rubber (SBR)) is evenly coated on a negative electrode current collector copper foil with a thickness of 6 μm, dried at room temperature, transferred to a 120°C oven for drying for 1 h, and then cold pressed and cut to obtain the negative electrode sheets.
[0074] Preparation of lithium-ion batteries: stack the positive electrode sheet, the isolation film, and the negative electrode sheet in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging foil, inject the electrolyte (solvent cyclic carbonate (EC), chain carbonate (DEC, DMC, EMC), the volume ratio of EC, DEC, DMC, EMC is 2:1:1:1; lithium salt LiPF6, the concentration of lithium salt is 1 mol / L; a small amount of additives such as VC, PS, LiPO2F2) into the dried battery cell, and obtain a lithium-ion battery after vacuum packaging, standing, formation, shaping and other processes.
[0075] Nail penetration test of lithium-ion batteries: At 25°C, the lithium-ion batteries were fully charged and then subjected to a nail penetration test, wherein the nail penetration rate was 100mm / s, the diameter of the steel nail was 3mm, and the nail penetration test was considered passed if the lithium-ion batteries did not explode or catch fire. Twenty lithium-ion batteries were tested in each group, and the nail penetration pass rate of the lithium-ion batteries was calculated.
[0076] Table 2 Performance of positive electrode current collector and lithium-ion battery
[0077]
[0078]
[0079] It can be seen from Table 2 that when the aluminum oxide is all in 6×10 -2 The coating is carried out under vacuum conditions, and the aluminum oxide layer has no defects. The resistivity of the obtained positive electrode current collector is large, and the nail penetration rate of the battery is not greatly affected.
[0080] Comparison between Example 1 and Comparative Example 2 shows that if all the aluminum metal is in 6×10 -2 The coating was carried out under vacuum conditions, the metal aluminum layer had no defects, the resistivity of the obtained positive electrode collector was not much different, but the nail penetration rate of the battery was significantly reduced.
[0081] It can be seen from the comparison between Example 1 and Comparative Example 3 that if the positive electrode current collector is not a multi-layer structure, the nail penetration rate of the battery will be significantly reduced.
[0082] The above is only a part of the embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode current collector, characterized in that: include: Base film, multi-layer metal aluminum layer and multi-layer aluminum oxide layer; The aluminum oxide layer and the metal aluminum layer are alternately overlapped in sequence on at least one surface of the base film, the aluminum oxide layer is in contact with the surface of the base film, and among the multiple aluminum oxide layers, the aluminum oxide layer in contact with the base film has a dense structure, and the aluminum oxide layer not in contact with the base film has a porous structure. The metal aluminum layer has a porous structure, and the two metal aluminum layers on the two surfaces of the aluminum oxide layer are connected through the holes on the aluminum oxide layer not in contact with the base film.
2. The positive electrode current collector according to claim 1, characterized in that: The total thickness of the multi-layer aluminum oxide layer is 1%-20% of the total thickness of the multi-layer metal aluminum layer.
3. The positive electrode current collector according to claim 2, characterized in that: The total thickness of the metal aluminum layer and the aluminum oxide layer is 600-2400 nm, the number of layers of the metal aluminum layer is 10-30, and the number of layers of the aluminum oxide layer is 10-30.
4. The positive electrode current collector according to claim 1, characterized in that: The base film has a thickness of 2.6-12 μm.
5. The positive electrode current collector according to claim 4, characterized in that: The base film is selected from one of OPP film, PET film, PI film, PS film, PPS film, CPP film, PEN film, PVC film, PP film, PE film and non-woven fabric film.
6. The positive electrode current collector according to any one of claims 1 to 5, characterized in that: The aluminum oxide layer and the metal aluminum layer are alternately overlapped in sequence on both surfaces of the base film.
7. The positive electrode current collector according to claim 6, characterized in that: The resistivity of the positive electrode current collector is (5.0-15.0)×10 -8 Ω.m.
8. A method for preparing a positive electrode current collector according to any one of claims 1 to 7, characterized in that: include: The aluminum oxide layer and the metal aluminum layer with a porous structure are alternately overlapped in sequence on at least one surface of the base film, and the two metal aluminum layers on the two surfaces of the aluminum oxide layer are connected through the holes on the aluminum oxide layer.
9. The preparation method according to claim 8, characterized in that: The method for forming the metal aluminum layer having a porous structure comprises: The vacuum degree of the coating environment is (1.0-9.0)×10 -1 Pa; The method for forming the aluminum oxide layer comprises: Oxygen is firstly adsorbed on the surface of the evaporated film, and then the evaporated aluminum atoms react with the oxygen to form the aluminum oxide layer on the surface of the evaporated film.
10. The preparation method according to claim 9, characterized in that: When the aluminum oxide layer contacting the surface of the base film is formed, the vacuum degree of the coating environment is (1.0-9.0)×10 -2 Pa; When the aluminum oxide layer not in contact with the surface of the base film is formed, the vacuum degree of the coating environment is (1.0-9.0)×10 -1 Pa.
Citation Information
Patent Citations
Lithium battery with novel current collectors and preparation method of lithium battery with novel current collectors
CN107154499A
All-solid state battery
CN109755659A
Mass flow body and electrochemical energy storage device
CN206878100U
Positive current collector, positive pole piece and secondary battery
CN216145647U